Effects of dofetilide and ranolazine on atrial fibrillatory rate in a horse model of acutely induced atrial fibrillation. (28th January 2019) - Carstensen, Helena; Hesselkilde, Eva Zander; Haugaard, Maria Mathilde; Flethøj, Mette; Carlson, Jonas; Pehrson, Steen; Jespersen, Thomas; Platonov, Pyotr G.; Buhl, Rikke
Abstract: Introduction: The atrial fibrillatory rate is a potential biomarker in the study of antiarrhythmic drug effects on atrial fibrillation (AF). The purpose of this study was to evaluate whether dose‐dependent changes in the atrial fibrillatory rate can be monitored on surface electrocardiography (ECG) following treatment with dofetilide, ranolazine, and a combination of the two in an acute model of AF in horses. Methods and Results: Eight horses were subjected to pacing‐induced AF on 4 separate days. Saline (control), dofetilide, ranolazine, or a combination of dofetilide and ranolazine was administered in four incremental doses. Atrial fibrillatory activity was extracted from surface ECGs using spatiotemporal QRST cancellation. The mean atrial fibrillatory rate before drug infusion was 297 ± 27 fpm. Dofetilide reduced the atrial fibrillatory rate following the infusion of low doses (0.89 µg/kg, P  < 0.05) and within 5 minutes preceding cardioversion ( P  < 0.05). Cardioversion with ranolazine was preceded by a reduction in the atrial fibrillatory rate in the last minute ( P  < 0.05). The combination of drugs reduced the atrial fibrillatory rate in a similar manner to dofetilide used alone. A trend toward a lower atrial fibrillatory rate before drug infusion was found among horses cardioverting on low doses of the drugs. Conclusion: The atrial fibrillatory rate derived from surface ECGs showed a difference in the mode of action on AF between dofetilide and ranolazine. Dofetilide reduced the atrial fibrillatory rate, whereas ranolazine displayed a cardioverting mechanism that was distinct from a slowing of the fibrillatory process.